Web-based matching system for friend recommendation - Ang, Shu Hui (Nanyang Technological University, 2023)
NiceToMeetU (NTmU) is developed as a friend recommendation platform using Django Framework for Nanyang Technological University (NTU) students to make friends in school. The platform makes use of the content-based filtering recommendation system to match users based on their profiles, which are constructed from 4 aspects - personality traits, movies, hobbies, and music in the ratio of 4:3:2:1. The previous version classified users into 16 Myers Briggs Type Indicator (MBTI) personality type across 4 axes using BERT model.